Τὰ Ὅπλα Τῶν Γεφυρέων Of The Persian War: Herodotus On The Banishment Of The Barbarians Out Of Europe And The Issue Of The Completeness Of The First „The Histories” - Sinitsyn, Aleksandr (Acta Archaeologica Lodziensia, 2019)
The article discusses the principal “Herodotean question” of the completeness of the work done by the historian. How well did Herodotus manage to accomplish his design? Should we regard his work in the form it has reached us as complete and integral? Or does it end abruptly at the events of 479/8 BC, despite “the Father of History” having planned to continue his account of the Greek-Persian wars? Over the last century and a half, pluralism in the views the researchers on the issue of the completeness of Herodotus’ work has emerged. The author ventures some observations on the finale of the The Histories and draws our attention to the passage Hdt. 9.121 in which Herodotus emphasizes the fact that the barbarians transgressing the geographical boundaries of Europe had been punished: the cables of the bridges which the Persians had used to tie Asia and Europe were taken to Hellas by the victors. According to the author, the historian’s testimony τὰ ὅπλα τῶν γεφυρέων ὡς ἀναθήσοντες ἐς τὰ ἱρά symbolizes the end of the war against the Barbarian, hence, the accomplishment of Herodotus’ design – the completion of the account of “great and marvellous deeds done by Greeks and foreigners and especially the reason why they warred against each other”.